A Macrocyclic Ligand Framework That Improves Both the Stability and T1-Weighted MRI Response of Quinol-Containing H2O2Sensors - Karbalaei, Sana; Knecht, Erik; Franke, Alicja; Zahl, Achim; Saunders, Alexander C.; Pokkuluri, P. Raj; Beyers, Ronald J.; Ivanović-Burmazović, Ivana; Goldsmith, Christian R. (Inorganic Chemistry, 2021)
Previously prepared Mn(II)- and quinol-containing magnetic resonance imaging (MRI) contrast agent sensors for H2O2 relied on linear polydentate ligands to keep the redox-activatable quinols in close proximity to the manganese. Although these provide positive T1-weighted relaxivity responses to H2O2 that result from oxidation of the quinol groups to p-quinones, these reactions weaken the binding affinity of the ligands, promoting dissociation of Mn(II) from the contrast agent in aqueous solution. Here, we report a new ligand, 1,8-bis(2,5-dihydroxybenzyl)-1,4,8,11-tetraazacyclotetradecane, that consists of two quinols covalently tethered to a cyclam macrocycle. The macrocycle provides stronger thermodynamic and kinetic barriers for metal-ion dissociation in both the reduced and oxidized forms of the ligand. The Mn(II) complex reacts with H2O2 to produce a more highly aquated Mn(II) species that exhibits a 130% greater r1, quadrupling the percentile response of our next best sensor. With a large excess of H2O2, there is a noticeable induction period before quinol oxidation and r1 enhancement occurs. Further investigation reveals that, under such conditions, catalase activity initially outcompetes ligand oxidation, with the latter occurring only after most of the H2O2 has been depleted.
CRIS-Team Scopus Importer:2021-07-02